2006
DOI: 10.3200/joer.100.1.35-43
|View full text |Cite
|
Sign up to set email alerts
|

Gender in Schools: A Qualitative Study of Students in Educational Administration

Abstract: Students who aspire to become school principals and superintendents must be prepared to lead schools committed to serving boys and girls equitably. In this qualitative study, 122 graduate students in a cultural diversity course maintained journals of their experiences. The authors kept records of teaching the course and of selected written assignments given to the students, according to Interstate School Leaders Licensure Consortium standards, which drive reform in school leadership. From analysis of all writt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…Booher-Jennings 2008; Mastekaasa and Smeby 2008). Though women have made gains in college enrolment and now outnumber men as undergraduate students in higher education (58% to 42%) (Peter and Horn 2005), men still score higher on standardised tests and outnumber women in high-paying jobs (Andrews and Ridenhour 2006). Additional research (e.g.…”
mentioning
confidence: 97%
“…Booher-Jennings 2008; Mastekaasa and Smeby 2008). Though women have made gains in college enrolment and now outnumber men as undergraduate students in higher education (58% to 42%) (Peter and Horn 2005), men still score higher on standardised tests and outnumber women in high-paying jobs (Andrews and Ridenhour 2006). Additional research (e.g.…”
mentioning
confidence: 97%
“…This would then theoretically open the doors to a wider variety of careers and help close the occupational gender gap. Andrews and Ridenour (2006) found similar results in regards to educating individuals about stereotypes and increasing awareness about their prevalence. As the participants in this study became more aware of the negative effects of gender stereotypes, they began to adopt more gender fair practices and decrease the instances of stereotyping.…”
Section: Gender Stereotypessupporting
confidence: 70%
“…Also, education about gender stereotyping appears to decrease gender stereotyping. Andrews and Ridenour (2006) assessed the beliefs and attitudes about gender issues of education graduate students who were enrolled in a cultural diversity course. The authors found that throughout this course these students became more aware of gender stereotyping and the negative effects of this process, tended to adopt more gender fair practices in the classroom, and became more aware of gender discrimination and power differences that were based on gender.…”
Section: Impact Of Gender Role Socializationmentioning
confidence: 99%
“…Programs advocating knowledge and awareness of gender stereotyping appear to have helped to decrease the process of gender stereotyping and made it easier for men to pursue nontraditional careers (Andrews & Ridenour, 2006). Sax and Bryant (2006) surveyed 17,637 students attending baccalaureate institutions across the United Stated and found that several aspects of the college environment, including the peer culture, faculty interaction, and curriculum, all influenced students to shift either toward or away from nontraditional career choices.…”
Section: Impact Of Gender Role Socializationmentioning
confidence: 99%